Do I-PASS for FAIR? Measuring the FAIR-ness of Research Organizations - J. Ringersma (Ubiquity Press, 2021)
Given the increased use of the FAIR acronym as adjective for other contexts than data or data sets, the Dutch National Coordination Point for Research Data Management initiated a Task Group to work out the concept of a FAIR research organization. The results of this Task Groups are a definition of a FAIR enabling organization and a method to measure the FAIR-ness of a research organization (The Do-I-PASS for FAIR method). The method can also aid in developing FAIR-enabling Road Maps for individual research institutions and at a national level. This practice paper describes the development of the method and provides a couple of use cases for the application of the method in daily research data management practices in research organizations.